The effects on boar reproductive efficiency of exposure to females during rearing - Duane L Davis; J V Craig; Jim L Nelssen; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1980)
Thirty-two boars (16 littermates) were reared from 3½ to 5½ months in either an all-male group or with fence-line exposure to cycling sows and gilts. Exposure to females did not significantly increase testicle or accessory gland weights, sperm production, or libido score. Boars that displayed more sexual activity (mounts and sheath sniffs) from 3½ to 5½ months of age performed superiorly in mating tests at 5½ and 7½ months of age. Libido scores of littermate boars were very similar.; Swine Day, Manhattan, KS, November 13, 1980
Keywords: Swine day; 1980; Kansas Agricultural Experiment Station contribution; no. 81-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 388; Swine; Boars; Reproductive efficiency; Rearing